Low Loss THz Waveguides and Its Potentials towards 6G Communication: A Brief Chronicle Review - Arslan Ahmed Sohoo, Arslan Ahmed Sohoo; Che Seman, Fauziahanim; Yee See Khee, Yee See Khee; Awang, Noor Azura; Izhar Ahmed Sohu, Izhar Ahmed Sohu (2023)
Advancement in technology has opened the doors for the terahertz (THz) frequency range to be applied in different fields for various applications. The future communication technology, especially 6G, will also intend to utilize the THz frequency band due to its large bandwidth that has the capabilities to achieve a high data rate. Great losses are presented in the early research into terahertz transmission medium. It is critical to design an appropriate waveguide that can integrate the THz waves into the system efficiently with minimum loss and provides the ease of transmission of data and overcomes the free space loss issues. Communication, sensing, and other application parameters are highly affected by transmission losses; therefore, low transmission loss and dispersion loss waveguide designs are required for proper utilization. In this paper, the review on reduction in the transmission loss in different types of waveguides operating at the Terahertz frequency range is studied. The design and the experimental setup for several classes of THz waveguides for minimizing transmission loss are also discussed. The review study shows that these waveguides can be a promising transmission medium for future 6G communication